Rumi’s Human-Centered Moral Pedagogy for Teachers in the Age of Artificial Intelligence - Labib Mustofa; Bakhruddin Fannani; Mohammad In'am Esha; Faridatun Nikmah; Rizwan Sahib; Ahmad Arofat; Regina Della Adibah (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Although the growing use of artificial intelligence in education has transformed instructional practices, research addressing its implications for the moral and human dimensions of teachers’ roles remains limited. This study examines a human-centered moral pedagogy derived from Fihi Ma Fihi by Jalaluddin Rumi in response to these challenges. A qualitative approach was employed using a hermeneutic design. The primary data source was Fihi Ma Fihi, supported by Rumi’s other works, including Masnavi Ma’nawi, Diwan-e Shams Tabrizi, and Samudra Rubaiyat, as well as relevant scholarly literature. Data were collected through textual documentation and analyzed using thematic interpretation. The findings indicate that Rumi’s moral pedagogy emphasizes core virtues such as ṣabr, shukr, tawakkul, and khawf, which function as interconnected elements of inner transformation, emotional regulation, and ethical behavior. These values constitute a human-centered moral pedagogy that prioritizes internal moral awareness over external behavioral compliance. In the context of artificial intelligence, this framework redefines teachers’ roles from knowledge transmitters to facilitators of moral, emotional, and spiritual development. This study contributes to the theoretical development of moral pedagogy by integrating Sufi ethical values into a human-centered educational framework relevant to AI-driven learning environments. It also offers pedagogical insights for teachers in Islamic education to foster reflective learning, ethical awareness, and meaningful engagement beyond technological efficiency. The study concludes that Rumi’s moral pedagogy provides a significant foundation for strengthening teachers’ roles in cultivating holistic human development in the age of artificial intelligence, while also highlighting the need for future empirical research on the implementation of this framework across diverse educational settings.